Some methodological/philosophical problems in secondary school science education : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University - Singh, Pravin (Massey University, 1983)
An examination of common images of science and the scientist, and of some conceptions of 'science processes' in secondary school science, as depicted in texts, curricula and other public utterances, reveals the influence of certain traditions of philosophy/methodology. The methodological/philosophical positions associated severally with Bacon, Locke and Hume, and the Logical Positivists, are collectively designated as 'Methodological Reductionism' in this study, and are explored and found to be inadequate and/or misleading in the light of recent developments in the philosophy of science. Dissatisfaction with current school science is also found to be a consequence of adoption of narrow, 'functional' goals of science education. Difficulties also arise from: confusion of meanings of scientific terms in relation to their 'ordinary language' usage as contrasted with their specialised scientific usage; teachers' attitudes towards, and understanding of, the nature of science; and teaching methods which despite innovations, have remained essentially content- oriented, fact-laden, formal and didactic. It is argued that if science education is to regain its interest and become educationally more meaningful for students, then an alternative methodological/philosophical rationale for science and 'science processes' is desirable. It is suggested that the adoption of what is basically a Kuhnian epistemology may help to remove misconceptions about science and the scientist, and also help to surmount some of the current difficulties in the teaching of science. To facilitate and accommodate conceptual changes in science education, a teaching and learning strategy based upon Kuhn's notions of 'paradigm' and 'paradigm change' can be utilised. Because current science education is said to be overly formalistic and socially isolated, it is recommended that a multi disciplinary approach may not only regain for science its declining interest, but also produce future citizens who are better equipped to deal with science/technology/ society problems and issues, and who will possess the cognitive and affective attributes needed for making a positive contribution within a science- and technology based society.
Keywords: Science; Study and teaching (Secondary)